Quantifying the Electronic Health Record Burden in Head and Neck Cancer Care - Ebbers, Tom; Kool, Rudolf B.; Smeele, Ludi E.; Takes, Robert P.; van den Broek, Guido B.; Dirven, Richard (Applied Clinical Informatics, 2022)
Background Although the main task of health care providers is to provide patient care, studies show that increasing amounts of time are spent on documentation.Objective To quantify the time and effort spent on the electronic health record (EHR) in head and neck cancer care.Methods Cross-sectional time–motion study. Primary outcomes were the percentages of time spent on the EHR and the three main tasks (chart review, input, placing orders), number of mouse events, and keystrokes per consultation. Secondary outcome measures were perceptions of health care providers regarding EHR documentation and satisfaction.Results In total, 44.0% of initial oncological consultation (IOC) duration and 30.7% of follow-up consultation (FUC) duration are spent on EHR tasks. During 80.0% of an IOC and 67.9% of a FUC, the patient and provider were actively communicating. Providers required 593 mouse events and 1,664 keystrokes per IOC and 140 mouse events and 597 keystrokes per FUC, indicating almost 13 mouse clicks and close to 40 keystrokes for every minute of consultation time. Less than a quarter of providers indicated that there is enough time for documentation.Conclusion This study quantifies the widespread concern of high documentation burden for health care providers in oncology, which has been related to burnout and a decrease of patient–clinician interaction. Despite excessive time and effort spent on the EHR, health care providers still felt this was insufficient for proper documentation. However, the need for accurate and complete documentation is high, as reuse of information becomes increasingly important. The challenge is to decrease the documentation burden while increasing the quality of EHR data.
Keywords: electronic health records; documentation burden; oncology; physician; interfaces; usability